Improving the technology of the synthesis of fatty acid monoglycerides using the glycerolysis reaction - Saveliev, Dmytro; Petrova, Olena; Yashchenko, Oleksandr; Rudakov, Serhii; Harbuz, Serhii; Shevchuk, Natalia; Kachanova, Tetiana; Gill, Michael; Bolhova, Nataliia; Borozenets, Nataliia (Eastern-European Journal of Enterprise Technologies, 2023)
The object of research is the process of fat glycerolysis in order to obtain fatty acid monoglycerides. Monoglycerides are an important component of chemical, pharmaceutical, cosmetic, and food industry products. These substances are used as emulsifiers, structure formers, complex formers, etc. The industrial production of monoglycerides involves the use of complex technologies, as well as dangerous and unstable catalysts. An urgent task is to develop new catalysts and improve technologies for monoglycerides obtaining. The technology for the synthesis of monoglycerides by the glycerolysis method, which involves the reaction of vegetable hydrogenated fat with glycerol, was studied. Potassium glyceroxide was used as a catalyst, which is effective and safe in terms of production and use. Hydrogenated unrefined fat according to DSTU 5040 (CAS Number 68334-28-1) was used. The fat has non-standard parameters: the melting point is 51 °C, the mass fraction of moisture and volatile substances is 0.3 %, the acid value is 3.2 mg KOH/g, the peroxide value is 7.6 ½ O mmol/kg. The process duration was 90 minutes, the glycerol concentration was 50 %. Rational conditions for glycerolysis were determined: catalyst concentration (1.5 %) and temperature (140 °C). Under these conditions, the product ensured the stability of the “water – sunflower oil” emulsion of 96.8 %, the concentration of monoglycerides in the system was 0.1 %. Product parameters: mass fraction of monoglycerides – 72.5 %, free glycerol – 1.5 %, acid value – 1.7 mg KOH/g. The research results make it possible to improve the glycerolysis process using a new catalyst and obtain monoglycerides with high emulsifying ability. This will increase the profitability of the enterprise and increase the volume of production of high-quality monoglycerides for various industries